The Souss-Massa River Basin, Morocco - Choukr-Allah, Redouane, 1953-; Ragab, Ragab; Bouchaou, Lhoussaine; Barceló, Damià (Springer, 2017)
This volume offers a comprehensive analysis of the water resources in the Souss-Massa river basin in southwestern Morocco and provides novel water-management approaches to narrow the gap between supply and demand for water. It evaluates conventional water resources−surface water and groundwater−and discusses in detail rainfall harvesting into dams along the Souss and Massa wadis. Further, it explores topics including the geology of the aquifer; the risk of over exploitation; alternative water resources, such as desalinated seawater and treated domestic wastewater, as well as management approaches like Data Development Analysis and the SALTMED model. With a focus on linking scientific research to practical applications and the demands of agriculture and associated agro-industry, urbanization and tourism, which compete for the limited water resources, the book appeals to environmental scientists, geologists, engineers and environmental managers.
Keywords: Hydrology -- Morocco.; Chemistry, Analytic.; Hydrogeology -- Morocco.; Water quality management -- Morocco.; Environmental chemistry.; Morocco.; elektronické knihy; electronic books